PandaMom – Feasibility and acceptability of an internet- and mobile-based intervention to enhance peripartum mental well-being and to prevent postpartum depression - Juliane Schmidt-Hantke; Bianka Vollert; Barbara Nacke; Franziska Hagner; Hannah Brüderl; Corinna Jacobi (Internet Interventions, 2024)
Background: Mental disorders during pregnancy and the postpartum period can have far-reaching consequences. To enhance peripartum mental well-being and prevent peripartum mental disorders, internet- and mobile-based interventions appear promising. They can overcome help-seeking barriers associated with face-to-face conditions and have proven to be effective. However, previous findings are scarce and mixed. The primary objectives of this study were to assess the feasibility and acceptability of an internet-based program aimed at enhancing peripartum mental well-being and preventing postpartum depression. Methods: In total, 149 pregnant, German-speaking women were assigned to the internet-based intervention PandaMom. The program comprises a total of 10 basic and supplementary modules related to pregnancy and postpartum, based on cognitive-behavioral principles. Additionally, PandaMom offers professional, individualized guidance and a moderated group-chat. Assessments were conducted at baseline (pre-intervention), as well as two and five weeks postpartum. The primary outcomes included feasibility, user satisfaction, and adherence to the intervention. Secondary outcomes included depressive symptomatology, anxiety and stress. Results: PandaMom was found to be feasible, and evaluation of module content and length satisfaction indicated that the intervention was well accepted. Nearly half of the participants utilized the guidance service by responding to individual messages from their intervention moderator. Regarding working alliance, participants reported a strong bond with their intervention moderator. Of the 149 participants, 132 logged into the platform at least once. 113 participants accessed at least one module, with an average of 4.7 modules opened per participant. However, only 16 participants completed the basic modules. Conclusion: The findings of this study support previous evidence that internet-and mobile-based interventions are feasible and acceptable during pregnancy and the postpartum period. Further research is needed to address the challenge of low adherence and to evaluate the efficacy of PandaMom.